PKPMPembinaan Sikap Religiusitas Dalam Penanggulangan Bahaya Narkoba Di Pimpinan Ranting Pemuda Muhammadiyah Kecamatan Percut Sei Tuan - Mario Kasduri; Mahmud Yunus Daulay (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2019)
The young generation becomes the hope of the nation and religion. If the young generation does not have good morals, they certainly cannot be leaders in the future. This is what happened at this time, many young people whose lives were only faltering without remembering their self-awareness and responsibility to become a moral and educated young generation.In realizing moral youth it takes a process that is committed to fostering especially to teach young people the importance of instilling Islamic values in themselves. If you don't have good morals, surely the young man will be destroyed and perish. Why can this be so, because we see the character of today's youth very weak and helpless because they are manipulated by the use of drugs.We see, especially throughout the city of Medan sub-district, how many millions of young people have their future destroyed due to the use of narcotics. This problem is a dilemma that must be able to be opposed by a useful science and fostering a religious attitude that can make the generation of teenage mosques to be smart in fighting drugs.Thus, religious attitudes are very important to be applied to adolescent mosques that are fostered through Muhammadiyah youth by helping to overcome the problem of drug abuse. This is the hope of all of us, how to be able to guide Muhammadiyah youth with Islamic values so that the young generation of the nation can stay away from actions that damage their future.